The Relationship between Shift Work and Burnout among ICU Nursing Staff in Hospitals of Shahid Beheshti University of Medical Sciences - Bakhtom, Shakiba; Nassiri, Parvin; Borgheipour, Hasti (Novelty in Biomedicine, 2019)
Background: Recent studies have indicated the high prevalence of burnout among nursing staff. Shift work is one of the characteristics of the nursing job; therefore, this study aimed to investigate the relationship between shift work and burnout among intensive care unit (ICU) nursing staff in hospitals of Shahid Beheshti University of Medical Sciences. Materials and Methods: This descriptive-analytic study of cross-sectional type was carried out the period of 2017-2018. The research population was of all nursing staff in the intensive care unit (ICU) in 7 public hospitals and 5 private hospitals. The sample size was 320 nursing staff that was surveyed by census method. To collect data, Maslach burnout inventory (with 78% and reliability and internal validity ranges from 71% to 92 %) and demographic profile questionnaire were used. All statistical analyses analyzed by SPSS software. Results: There was a significant relationship between emotional exhaustion and rotational shift work. There was no significant relationship between emotional exhaustion and night shift. There was a significant relationship between depersonalization and morning shifts in public hospitals. The shift component was only significant in the work shift of the evening and night of public hospitals with personal accomplishment as well. Conclusion: The shift work was considered as an effective factor in the burnout of nursing staff in ICU. By utilizing the results of the study, we can reduce the effects of shift work and make an appropriate intervention plan for promoting staff health.